Letter from Rev. W. T. Davidson to James Curtis Booth, April 5, 1859 - Davidson, W. T. (1859)
Reverend Davidson requests that James Curtis Booth (1810-1888) help to obtain a position at the United States Mint for a member of his congregation. Booth notes it is hopeless due to a glut of employees.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States